Discourse action of teachers and learners in oral interaction tasks in Spanish as second language. A case study - Calderón Espadas, Mario (Lenguas Modernas, 2015)
This research aim to get to know the resources used by an expert teacher of Spanish as Second Language and her students in order to build the oral discourse in a task of oral interaction in group. We use a qualitative research methodology with ethnographic methods to generate data. We gather the data, select them, and examine a sample with ethnography of communication and discourse analysis. The results reveal that the elements that facilitate to the learners the collective construction of the oral discourse are the management of the participation and the organization of the the teacher’s discourse, the situation of interaction between equals, the use of strategies of autofacilitation, strategies of heterofacilitation and the collaborative work